2016
DOI: 10.1007/s00192-016-3133-2
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle training in groups versus individual or home treatment of women with urinary incontinence: systematic review and meta-analysis

Abstract: PFMT is an efficient technique for the improvement of the symptoms of female UI. When PFMT was supervised by a physiotherapist, no significant difference was noted when comparing group with individual approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 30 publications
2
41
0
3
Order By: Relevance
“…[15][16][17] The evidence from these studies was inconclusive and researchers have highlighted the need for additional studies in this area. 18 Thus, this study aims to assess the effect of home-based PFMT in comparison to a group of subjects with no training, on decreasing the severity of symptoms of SUI, improving QOL, and strengthening PFM among Omani women.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The evidence from these studies was inconclusive and researchers have highlighted the need for additional studies in this area. 18 Thus, this study aims to assess the effect of home-based PFMT in comparison to a group of subjects with no training, on decreasing the severity of symptoms of SUI, improving QOL, and strengthening PFM among Omani women.…”
Section: Introductionmentioning
confidence: 99%
“…5 A meta-analysis found improvement in UI symptoms following individual or group PFMT under the supervision of a physical therapist. 6 The benefits of group interventions may be related to biopsychosocial aspects. 7 On the other hand, individual PFMT can improve awareness of pelvic floor muscle (PFM) contraction.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis found improvement in UI symptoms following individual or group PFMT under the supervision of a physical therapist 6 . The benefits of group interventions may be related to biopsychosocial aspects 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors suggested that PFMT performed in group may be a viable option for the public health system, since it is possible to treat more women during a shorter period of time with low cost. 25 The present study was initiated in January 2016 and is currently active. The results of this study can guide physical therapists in choosing the treatment format of stress urinary incontinence, indicating whether the training of the pelvic floor muscles, which starts individualized and progresses to group treatment, would be more effective than only individual or only group treatment.…”
Section: Discussionmentioning
confidence: 99%